The Training for Soft Skills Development for Youth in Kadumaneuh Village, Pandeglang, Banten - Budiman, Andika Nuraga; Nurhayati, Ely; Subing, Hesty Tambuati; Suyana, Hilma (Entrepreneurship and Community Development, 2024)
Based on the Village Development Index figures released by the Ministry of Villages, Development of Disadvantaged Regions and Transmigration, Kadumaneuh Village in Pandeglang Regency is a village that is included in the developing village group. Relevant training is carried out in the village, one of which is soft skills training for the youth of Kadumaneuh Village, Pandeglang Regency, as energetic and innovative village drivers. Community development activities in Kadumaneuh Village aim to help the young find the best jobs to improve the welfare of the village community and provide training on soft skills that young people must have to become competent individuals in the future who can develop Kadumaneuh village. The method used in implementing this activity is training and is supported by a set of computer tools to access all information about work and increase their skills. The development of soft skills can have various positive implications. Young people who have these skills will more easily get jobs in both the formal and informal sectors, and they can be better at marketing village products and establishing collaboration with outside parties. Soft skills also include learning abilities; young people will find it easier to access information, and youth can participate actively in the village development decision-making process.